Development of cheese flavor for snack foods using enzyme-modified kesong puti - Consolacion, Sheila Marie D.; Dumelod, Benelyn Domingo (2000., 2000)
ABSTRACT This study aimed to produce a cheese flavor applicableto snack foods using kesong puti by commercial enzyme application. Two enzyme modification approaches were employed: the one-step and the component approaches. ENEZECO Fungal Protease Concentrate and ENEZECO Lipase RO 100 were applied to the cheese for the enzymatic processes. Phase I dealt with the production and characterization of the native cheese prior to enzyme modification. A descriptive test was conducted to determine the sensory attributes of the native cheese. The pH, moisture, crude fat, and crude protein contents were also determined. Phase II dealt with the determination of the better enzyme-modification approach. Through a acceptance test, the one-step approach of enzyme-modification was found to produce a more distinct cheddar flavor. Phase III dealt with the determination of the concentration of enzyme-modified cheese that would produce good cheese flavor with less perceptible flavor defects. The incorporation of 30% enzyme-modified cheese produced through one-step approach gave the more distinct cheese flavor with no pronounced flavor defects. In Phase IV, the cheese powder with 30% w/w enzyme-modified kesong puti was compared to a commercial cheese powder. The cheese powder with enzyme-modified native cheese was found to have a cheddar aroma comparable with the commercial cheese powder. Improvement in flavor and form of the cheese powder is still needed.
Thesis (BSFT)-- University of the Philippines Diliman
Keywords: Snack foods; Cheese